Self-healable and reprocessable acrylate-based elastomers with exchangeable disulfide crosslinks by thiol-ene click chemistry. (6th January 2021) - Gao, Hong; Sun, Yingchun; Wang, Miaomiao; Wu, Bo; Han, Guoqiang; Jin, Ling; Zhang, Kui; Xia, Youyi
Abstract: Non-reprocessable thermosets and elastomers are causing more and more environmental issues. Acrylate-based elastomers with self-healing and reprocessing capability are highly desired. As dynamic covalent chemistry provides a new ground to address these issues, the present article synthesized a novel kind of acrylate-based elastomers with exchangeable disulfide crosslinks, particularly, by virtue of the thiol-ene click reactions between acrylate monomers and polysulfide oligomers. We also investigated and compared thiol-ene click reactions via different approaches, including by radical pathways, such as redox-initiator system and photo-initiator system, or via catalytic processes mediated by bases. These novel acrylate-based elastomers are capable of self-healing and reprocessing in a rapid and efficient manner, and the self-healing and reprocessing efficencies are related to the elastomer structures formed by different synthetic strategies. Notably, the base system without the extra addition of self-healing catalyst are found especially efficiently and the mechanical properties of acrylate-based elastomers can be restored more than 90% with a habitation of 5 h. Such rapid and efficient restoration suggests a highly promising application as recoverable adhesives in practice. Those results open up a novel avenue for the designation and synthesis of acrylate-based elastomers and thermosets with self-healing and reprocessing properties, among other desirable functions. Graphical abstract: Image 1 Highlights: Self-healable acrylate-based elastomers with dynamic covalent bonds. Acrylate-based elastomers prepared by thiol-ene click chemistry. Thiol-ene click chemistry performed by radical and base catalytic pathways. Good self-healing and reprocessing properties. No need for additional self-healing catalyst in alkali system.